Employers’ Placement Expectations in Agricultural Graduates of Tamil Nadu Agricultural University - T.R., Sridevi Krishnaveni; Arunachalam, R. (Indian Journal of Extension Education, 2020)
The study was designed to identify the factors fixed to be the parameter by the job providers during placements of agricultural graduates. Twelve parameters were identified for understanding the preference during recruitment of agricultural undergraduates and they were found to fall under dimensions like education, personality and socio economic traits. 34 active job providers in the field of agriculture were identified. A structured mailed questionnaire was prepared and used for the data collection. Results showed that the preferential behavior of job providers was highly diversified based on the nature of job and the job requirement. It was found that the degree of expectation as a whole was found to be low to medium to support underprivileged and struggling students. The job providers were not very rigid or over demanding in selecting an eligible candidate. The preference was given mostly to knowledge, skill and personality rather to socio, economic status.
Keywords: Agricultural undergraduates; Employer preference; Employer’s expectations; Job provider’s requirement; TNAU